The Role of Simulation in Reducing Disturbance at Production Line - Norhanom, Awang (Universiti Malaysia Pahang, 2012)

(untitled)
This study aims to present a significant role of simulation in production flow in automotive industry in Malaysian using discrete-event simulation (DES). This was based on data collection in Painting Shop (PS) in production manufacturing plant. Case experiences indicate that combining data analysis with DES is beneficial in identifying and reducing disturbance or constraints in manufacturing system. The computer simulation enables the reduction of disturbance and constraint in existing capacity suggested improvement in productivity than existing production operation. The study makes a business case that process improvement through reduction of disturbance and constraint can be effectively accomplished with the integrated approach of using widely available inexpensive and user-friendly computer-based tools.